Mendelian randomization study on the causal relationships among fasting blood glucose, plasma proteins, and squamous cell lung cancer - Ronglin Li; Zhenniu Lei; Zhaoke Wen; Yifan Zhou; Yunzhi Ma; Junqi Qin; Xiaoyan Huang; Shuping Huang; Shucong Peng; Shengjing Liang; Yonglong Zhong (Discover Oncology)
Abstract Background Squamous cell lung cancer (SQCLC) represents the second most common subtype of lung cancer (LC) with characteristics of treatment resistance. Plasma proteins often influence levels of fasting blood glucose (FBG), consequently impacting LC. However, the precise role of FBG in this association remains unclear. Objective To investigate the causal relationships of FBG with LC and its subtypes, plasma proteins, and SQCLC, as well as the mediating role of FBG. Methods Mendelian randomization (MR) analysis was employed to assess the causal associations of FBG with LC and its subtypes, plasma proteins and SQCLC, and plasma proteins and FBG, using the two-step MR approach with the primary method being Inverse Variance Weighted (IVW). Protein–Protein Interaction (PPI) network was utilized to identify hub genes of plasma proteins causally linked to SQCLC. Results FBG was a risk factor for SQCLC (OR: 1.376, 95% CI 1.017–1.862, P = 0.038) but had no significant causal associations with LC and other subtypes (P > 0.05). Furthermore, 54 plasma proteins had significant causal associations with SQCLC (P < 0.05). EEF2 K (OR: 1.111, 95% CI 1.015–1.216, P = 0.023) and SSR1 (OR: 0.546, 95% CI 0.487–0.613, P < 0.001) were identified as a risk and protective factor for FBG, respectively. Mediation analysis indicated a significant negative mediating effect of FBG in the causal relationship between SSR1 and SQCLC (B = − 0.193, 95% CI − 0.312–0.074, P = 0.001), with a mediation proportion of 44.4%. Conclusion Our study revealed FBG as a risk factor for SQCLC and demonstrated the mediating role of FBG in the causal association between SSR1 and SQCLC.